Botany for Degree Students : Fungi - B R Vashishta and others; Vashishta, B R; Sinha, A K; Kumar, Anil (New Delhi S Chand and Company Ltd, 2020)
t is a part of five book series on Botany for Degree Students. The revised edition of Botany for Degree Students-Bryophyta deals with a small group of primitive, thalloid plants which are amphibious in habit. The text presents latest and significant results of botanical researches in an organised, lucid and cogent manner. This book is suitable for both undergraduate and postgraduate courses.
Keywords: Myxomycotina; Hemiascomycetidae; Plant Parasitic Nematodes; Eumycotina